The Impact Of Human Resource Management Practices and Organizational Culture on Organizational Citizenship Behavior in Indonesian Sharia Banks - Putrini, Nadia; Satrya, Aryana (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2023)
The research investigates the effect of Human Resource Management (HRM) practices and organizational culture on Organizational Citizenship Behavior (OCB), with organizational commitment as a mediating factor. The study aims to explore viable solutions and recommendations for improving OCB in Sharia Banks located in the Special Capital Region of Jakarta (DKI Jakarta). This study uses a quantitative approach using a questionnaire survey given to 260 permanent employees who work at Sharia Banks in DKI Jakarta. The collected data were analyzed using SEM-PLS to test the relationship between various variables. The findings of this study revealed that HRM practices and organizational culture have significant direct and indirect effects on OCB through the mediating role of organizational commitment. The results also showed that the proposed model achieved a good model fit, and HRM practices and organizational behavior have an indirect impact on OCB mediated by employee organizational commitment. In addition, the magnitude of the indirect impact of HRM practices was found to be significantly greater than the direct impact.